Smittskydd - Språkbanken Text (University of Gothenburg, 2024)
The newspaper Smittskydd by Smittskyddsinstitutet (Swedish Institute for Communicable Disease Control) 2002–2010

Smittskyddsinstitutets tidskrift Smittskydd, årgångarna 2002–2010
Smittskydd
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik